REPRESENTASI NILAI-NILAI BUDAYA DALAM WACANA PERNIKAHAN ADAT JAWA: KAJIAN ETNOLINGUISTIK PADA UPACARA TEMU MANTEN - Ali Manshur; Ahmad Azwar Anas (Jurnal PENEROKA, 2026)
This study aims to uncover the discourse, cultural meaning, and symbolism in the Temu Manten procession in Javanese traditional weddings. The scope of the research focuses on the Temu Manten procession in Javanese traditional weddings as a semiotic system that combines ritual speech, symbolic actions, and value structures. This study uses a qualitative method with an ethnolinguistic approach. Data were obtained through participatory observation, in-depth interviews, documentation, and recording of the procession in Kedungwungu Village, Banyuwangi. The results show that prayers, mantras, advice, and ritual dialogue function as a medium for preserving the noble values ??of Javanese society, such as harmony, loyalty, respect for parents, and balance in life. Each stage of the procession, including panggih, balangan gantal, wijikan, pecah wiji aji, junjung prajat, kacar-kucur, and sungkeman, contains cultural symbols that build philosophical meanings about responsibility, partnership, and spirituality in the household. The interaction between language and ritual actions shows that Temu Manten is a semiotic system that unites social structures, traditional practices, and cultural identities. An interesting finding in this study demonstrates that ritual language serves as a medium for storing cultural values ??and binding social structures within Javanese communities. The interaction between language and ritual actions demonstrates that Temu Manten is a semiotic system that unites cultural identity, traditional practices, and intergenerational social relations. These findings are expected to contribute to ethnolinguistic studies and the preservation of Javanese wedding traditions amidst contemporary social change